Competition amplifies drought stress in forests across broad climatic and compositional gradients. Issue 7 (14th July 2017) - Gleason, Kelly E.; Bradford, John B.; Bottero, Alessandra; D'Amato, Anthony W.; Fraver, Shawn; Palik, Brian J.; Battaglia, Michael A.; Iverson, Louis; Kenefic, Laura; Kern, Christel C.
Abstract: Forests around the world are experiencing increasingly severe droughts and elevated competitive intensity due to increased tree density. However, the influence of interactions between drought and competition on forest growth remains poorly understood. Using a unique dataset of stand‐scale dendrochronology sampled from 6405 trees, we quantified how annual growth of entire tree populations responds to drought and competition in eight, long‐term (multi‐decadal), experiments with replicated levels of density (e.g., competitive intensity) arrayed across a broad climatic and compositional gradient. Forest growth (cumulative individual tree growth within a stand) declined during drought, especially during more severe drought in drier climates. Forest growth declines were exacerbated by high density at all sites but one, particularly during periods of more severe drought. Surprisingly, the influence of forest density was persistent overall, but these density impacts were greater in the humid sites than in more arid sites. Significant density impacts occurred during periods of more extreme drought, and during warmer temperatures in the semi‐arid sites but during periods of cooler temperatures in the humid sites. Because competition has a consistent influence over growth response to drought, maintaining forests at lower density may enhance resilience to drought in all climates.